Penang Tourism Attractions And Attraction Attributes - Cheah, Erleen Li-Ling (2014)
The objectives of this study are to investigate on tourism attractions and its attraction attributes in the state of Penang context. This study also intended to examine the relationship between attraction attributes of heritage destination and tourist satisfaction towards the heritage destination. The tourist demographics had been included in this study to explore the moderating effect and the relationship between tourist demographics, attraction attributes and tourist satisfaction. In practical sense, this study is an effort to determine the overall performance of tourism attractions in the state of Penang as the World Heritage Site and the impact of the enlistment.